Fluid flow through replicated microcellular materials in the Darcy-Forchheimer regime. (March 2017) - Weber, L.; Ingram, D.; Guardia, S.; Athanasiou-Ioannou, A.; Mortensen, A.
Abstract: We extend here a "bottleneck" flow model derived earlier for incompressible fluids flowing under creeping flow conditions [Despois, J. and Mortensen, A: Acta Materialia 53 (2005) 1381] to flow regimes where inertial losses are no longer negligible, causing the governing flow law to deviate from Darcy's law and become the Darcy-Forchheimer law. The proposed law is compared with measurements of the Darcian permeability K D and of the Forchheimer coefficient C in forced-flow of air through microcellular aluminium made by the replication process. The geometrical features of the cellular medium are varied in terms of volume fraction of porosity (in the range of 0.66–0.86) and the average cell diameter from (108–425 μm). As found previously in measurements with water, the Darcy permeability of the foams for airflow is also reasonably well captured by the model. In the Forchheimer-regime the model gives good quantitative agreement with data if one assumes that the amount of air kinetic energy that is dissipated when passing across each bottleneck linking one pore to its neighbour along the fluid flow path corresponds to the difference, in a stream of constant cross-sectional area, between a uniform fluid velocity profile and the non-uniform profile that is created by the no-slip condition along the window boundary. Graphical abstract: Image